Pilgrimage as connective tissue: what you see is not always what you get - Zaidi, Saiyyidah (2023)
This paper is based on a keynote presentation given at the British and Irish Association of Practical Theology (BIAPT) 2022 online conference with the theme ‘Flesh & Blood: Embodiment & Practical Theology.’ It is an Islamic tradition when beginning a talk, or giving a paper, to start by giving praise to God and I would like to do that, and to say that any good in this material is from God and any mistakes are my own. It is a huge honour for me to be delivering this keynote. I am here as the product of my mentors, teachers and friends and I would like to thank them all. In this paper I share my unexpected journey to Rome, Italy. First, to avoid misunderstandings and miscommunication I will explore brief definitions. I will then turn to author reflexivity and methodology. Second, I share four autoethnographic vignettes written to explore the theme of embodiment and Practical Theology from the perspective of a Brown-British-Muslim-Woman. Third, I discuss themes of intersectionality and embodiment, and offer some thoughts on what we may do to get to know one another.
Keywords: Muslim; keynote; autoethnography; Embodiment